2005
DOI: 10.1177/002242940505300303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Training and Musical Complexity on Focus of Attention to Melody or Harmony

Abstract: The purpose of this study was to investigate the relationships between music training and musical complexity and focus of attention to melody or harmony. Participants ( N= 192) were divided into four groups: university jazz majors ( n= 64), other university music majors ( n= 64), high school instrumentalists ( n= 32), and junior high instrumentalists ( n= 32). The musical complexity variable consisted of four levels of melodic complexity and four levels of harmonic complexity each paired for a total of 16 poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…On the one hand, the use of chord labels or other conceptual labels in harmonic analysis can allow professionals to label chords in our block-chord stimuli and associate those labels with declarative knowledge about what pieces use those chords. On the other hand, increasing attention to chord progressions (Cullimore, 1999; Farbood, 2012; Williams, 2004) during practice (e.g., playing chords on an instrument) is likely to increase listeners’ general interest in harmony. Additionally, Wolpert (2000) found that musicians not only tend to pay more attention to harmony than non-musicians, but also tend to be more sensitive to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the use of chord labels or other conceptual labels in harmonic analysis can allow professionals to label chords in our block-chord stimuli and associate those labels with declarative knowledge about what pieces use those chords. On the other hand, increasing attention to chord progressions (Cullimore, 1999; Farbood, 2012; Williams, 2004) during practice (e.g., playing chords on an instrument) is likely to increase listeners’ general interest in harmony. Additionally, Wolpert (2000) found that musicians not only tend to pay more attention to harmony than non-musicians, but also tend to be more sensitive to it.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main challenges in studying how listeners mentally process harmony is not only that harmonic activity always entails some type of melodic and rhythmic activity, but that in most listening scenarios, melody and rhythm tend to be more perceptually salient than harmony (Cullimore, 1999; Farbood, 2012; Halpern, 1984; Mélen & Deliège, 1995; Williams, 2004). The perceptual prominence of rhythm and its influence on the mental processing of harmonic activity has traditionally been minimized in experimental settings by using moderately slow streams of same-duration events.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Schmuckler (1999), musical, or in this case melodic, complexity is, in and of itself, a psychologically intricate concept-one that has been a topic of a great deal of research in its own right (Arkes, Rettig, & Scougale, 1986;Conley, 1981;Eerola et al, 2006;Konečni, 1982;Rohner, 1985;Williams, 2004). Accordingly, the divergence between these sets of ratings might highlight those factors that are intrinsic to the notion of melodic complexity, but have little to do with contour structure per se.…”
Section: Discussionmentioning
confidence: 99%
“…Participants register responses by manipulation of a dial across a negative/positive continuum over a 256 degree arc. In nearly two decades of research, the CRDI has been shown to measure various responses to musical stimuli, including tension (Fredrickson, 2001), aesthetic response (Geringer & Madsen, 2003), song recognition and likeability (Parisi, 2004), and focus of attention to melody and harmony (Williams, 2005).…”
Section: Methodsmentioning
confidence: 99%